CEO, CFO, and board attributes' effect on fair value agriculture disclosure - Zaimah Abdullah; Sumaia Ayesh Qaderi; Arifatul Husna Binti Mohd Ariff; Sitraselvi Chandren; Rohaida Abdul Latif (Cogent Business & Management, 2023)
This study analyzed the current practice of Malaysian agricultural companies in disclosing their biological assets by examining the effect of chief executive officer (CEO), chief financial officer (CFO), and board attributes on fair value agriculture disclosure (FVAD), consequently proposing a standardized fair value disclosure model that could help agricultural companies to improve their FVAD. Based on disclosure paragraphs in MFRS 141 Agriculture, a comprehensive FVAD index was developed using the content analysis technique. Utilizing data from 84 firm-year observations for agricultural companies listed on the Bursa Malaysia from 2017 to 2019, regression analysis was performed to test the relationship of FVAD with the attributes of the CEO and CFO, and board characteristics. The regression results provided evidence of positive associations between FVAD and CEO educational background, CFO tenure, board size, and board independence. These results constitute important empirical inputs of a positive association between top executives' management attributes and accounting disclosure. Both CEO and CFO age were found to associate negatively with FVAD, and CEO tenure was found not to significantly affect FVAD. The findings from this study could shed some light on implementation in terms of corporate governance on the appointment of top management. To the best of our knowledge, this is one of the first studies to investigate the impact of CEO, CFO, and board characteristics on FVAD, particularly in Malaysia. It has also established a comprehensive index for measuring FVAD.
Keywords: 650; biological assets; corporate governance; disclosure; emerging market; fair value; upper echelons theory